A unified framework for incorporating decision making into explanations of business failure. Issue 7 (10th August 2015) - Amankwah-Amoah, Joseph
Abstract : Purpose: – The purpose of this paper is to examine how decision-maker attributes unfold to precipitate organisational failure. The analysis brings to light how key attributes such as information-processing capabilities and human capital decay interact to bring about business decline and exit. Design/methodology/approach: – The study is based on an integrated review and conceptualisation of the literature. Findings: – The study articulates how a set of attributes of decision makers, i.e. human capital obsolescence, powerlessness, meaninglessness and institutional linkages, contributes to organisational failure. Research limitations/implications: – The paper concludes by setting out an array of strategies of learning from others' failures. Originality/value: – In spite of a growing body of research on organisational failure, scholars have placed overwhelming emphasis on ecological explanations and business failure prediction models. The study moves beyond the ecological explanations to offer a more fine-grained analysis of firm-level factors that precipitate business failure.